Application of concentration and 2-dimensional stable isotope measurements of methane to constrain sources and sinks in a seasonally stratified freshwater lake [data] - Einzmann, Teresa; Schroll, Moritz; Kleint, Jan F.; Greule, Markus; Keppler, Frank (Universität, 2022)
Methane (CH4) emissions from aquatic systems have recently been comprised to account for up to 50 % of global CH4 emissions, with lakes representin...